HIJRAH PHENOMENON AMONG INDONESIAN MUSLIM MIDDLE CLASS: CURRENT CAUSES & CHALLENGES - Jati, Wasisto (Al-Qalam, 2023)
The word â€œhijrahâ€ has been familiar among Indonesian middle class recently. It basically refers to the re-adaption religious values in daily life especially for individual Muslims.Â  This attitude basically responds various issues such as life crisis, mental health issues, anxiety, and also increasing religious teaching demands. Therefore, committed with religion values would be the main answer for every problem.Â  Recently, â€œhijrahâ€ is not merely a personal matter, but it has been a collective norm that bound Muslims especially young people. As a collective norm, the â€œhijrahâ€ intention has responded wide issues. Most importantly, it seems that doing â€œhijrahâ€ has become an identity symbol rather spiritual motive.Â  Eventually, it might be a critical point to examine â€œhijrahâ€ phenomenon among Muslim middle class.Â  Following up these aforementioned gaps, this research would like to further investigate the recent shift of â€œhijrahâ€ movement that affected Muslim middle class. Drawing data on the critical literature review, this research shows that committed to â€œhijrahâ€ is a way to not only strengthen piousness but also how to bring Islam fits in with modernism. This has implication toward the way of religious expression in public space.Â